Effects of Physical Sample Approval Practice on Performance and Competitiveness of Export-Oriented Garment Industries in Ethiopia - Amare Abuhay (Journal of Engineering)
The textile sector is one of the major economic pillars in Ethiopia. The sector is generating foreign currency by exporting textile and finished garments. However, the competitiveness of this sector is not as per the expectation due to the long delivery time and excessive manufacturing cost. This study aims to assess the main approval processes in handling garment samples between manufacturers and buyers. The study also examines the effect of physical sample approval process on export performance and competitiveness of the industry. The study employed an explanatory and exploratory multiple-case study research approach in four apparel exporting companies. Both primary and secondary data were collected using questionnaires, semistructured interviews, and observation. Result from this study showed that the export performance and competitiveness of apparel industries are mainly affected by the traditional sample approval system due to long delivery time, unnecessary approval process cost, and poor inventory management of the sampling department. The result also indicates that long lead time and costly process system made the sector incompetent in international market. Therefore, it can be concluded that the apparel manufacturing and exporting industries in Ethiopia should modify their approach to nurture better speed and comparably lower process costs. Ethiopia’s apparel sector needs also to invest in creating a reliable quality manufacturing system to grow and meet government targets for expanding export sales.